Perencanaan Perluasan Hutan Kota Munjul, Provinsi DKI Jakarta - Andrianto Kusumoarto (LPPM, 2019)
Urban forest is one form of green open space that can contribute greatly to improving the quality of the environment. This study aims to plan the expansion of Munjul Urban Forest as an addition to the area of urban forest today. The method used is qualitative descriptive. The concept of Munjul Urban Forest development is a biological conservation. Based on the functions to be developed, the concept of space used for conservation, recreation, education. The onservation activities are planned for conservation of water, soil, and germplasm. The recreational activities are planned for outdoor recreation. The educational activity is planned for environmental education. The planned circulation path and facilities are used to support the functioning of conservation, recreation and education. Planning for expansion of Munjul Urban Forest is planned to provide spaces that are habitable and comfortable for users Key words: Urban Forest, Landscape Planning, Qualitative Descriptive, Biological Conservation